2015
DOI: 10.1007/s13277-015-4494-8
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer cell line MDA-MB-231 miRNA profile expression after BIK interference: BIK involvement in autophagy

Abstract: B-cell lymphoma 2 (BCL2)-interacting killer (apoptosis inducing) (BIK) has been proposed as a tumor suppressor in diverse types of cancers. However, BIK's overexpression in breast cancer (BC) and in non-small lung cancer cells (NSCLCs), associated with a poor prognosis, suggests its participation in tumor progression. In this study, we evaluated the global expression pattern of microRNAs (miRNAs), messenger RNA (mRNA) expression changes in autophagy, and autophagic flux after BIK interference. BIK gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…In addition to stimulating apoptotic pathways, Bik facilitates autophagy [2022] and enhanced autophagy is associated with poor clinical outcomes [2325]. Thus, using the gene expression microarray as a screening tool, we looked for a correlation between high Bik expression levels and markers of autophagy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to stimulating apoptotic pathways, Bik facilitates autophagy [2022] and enhanced autophagy is associated with poor clinical outcomes [2325]. Thus, using the gene expression microarray as a screening tool, we looked for a correlation between high Bik expression levels and markers of autophagy.…”
Section: Resultsmentioning
confidence: 99%
“…Bik was a target of autophagy and also actively contributed to autophagy induction [16]. Finally, silencing of endogenous Bik expression in the breast cancer cell line MDA-MB-231 downregulated crucial components of autophagic machinery [22]. We found that high Bik expression in breast cancer patients was significantly correlated with increased levels of the autophagy marker, ATG5.…”
Section: Discussionmentioning
confidence: 99%
“…27 Moreover, BIK controls the expression of miRNAs as well as the autophagic flux in MDA-MB-231 cells. 28 Thus, it would be interesting to investigate whether Star-PAP is involved in these new functions of BIK.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have demonstrated the potential role of SNCA in the pathological processes underlying human cancer. B-cell lymphoma 2 (BCL2)-interacting killer (apoptosis inducing) (BIK) controls the expression of autophagy-associated transcripts, such as SNCA , that participate in tumor progression in the breast cancer cell line MDA-MB-231 [ 34 ]. SNCA methylation in the stool could also serve as a promising biomarker for the detection of colorectal cancer [ 6 ].…”
Section: Discussionmentioning
confidence: 99%